Analysis and Design of Photobioreactors for Microalgae Production II: Experimental Validation of a Radiation Field Simulator Based on a Monte Carlo Algorithm - Heinrich, Josué Miguel (2012)
In previous study, we developed a methodology to assess the intrinsic optical properties governing the radiation field in algae suspensions. With these properties at our disposal, a Monte Carlo simulation program is developed and used in this study as a predictive autonomous program applied to the simulation of experiments that reproduce the common illumination conditions that are found in processes of large scale production of microalgae, especially when using open ponds such as raceway ponds. The simulation module is validated by comparing the results of experimental measurements made on artificially illuminated algal suspension with those predicted by the Monte Carlo program. This experiment deals with a situation, which resembles that of an open pond or that of a raceway pond, except for the fact that for convenience, the experimental arrangement appears as if those reactors were turned upside down. It serves the purpose of assessing as to what extent the scattering phenomena are important for the prediction of the spatial distribution of the radiant energy density. The simulation module developed can be applied to compute the local energy density inside Photobioreactors with the goal to optimize its design and their operating conditions